2022
DOI: 10.1097/corr.0000000000002333
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Long-term Survivorship of Primary and Revision Cemented Distal Femoral Replacements for Limb Salvage of Patients With Sarcoma?

Abstract: Background Cemented endoprosthetic reconstruction after resection of primary bone sarcomas has been in common use for decades. Although multiple studies have reported the survivorship of primary endoprostheses, implant survivorship after revision surgery is less well established. Given that earlier advances in systemic therapy improved survival of patients with sarcoma, the usage of revision endoprostheses can be expected to increase and, as such, understanding revision implant survivorship will help to inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In the current study, Geiger et al [6] reported very long-term results using large-registry data about primary and revision cemented DFRs, which provided valuable information that would not easily be obtained in other ways. The authors found that revision DFR has poorer overall 15-year, 20-year, and 25-year implant survival than primary DFRs do.…”
Section: Where Are We Now?mentioning
confidence: 87%
See 3 more Smart Citations
“…In the current study, Geiger et al [6] reported very long-term results using large-registry data about primary and revision cemented DFRs, which provided valuable information that would not easily be obtained in other ways. The authors found that revision DFR has poorer overall 15-year, 20-year, and 25-year implant survival than primary DFRs do.…”
Section: Where Are We Now?mentioning
confidence: 87%
“…In this study, Geiger et al [6] discovered that stem diameters less than 15 mm in revision cemented DFRs are associated with stem fatigue fractures and aseptic loosening resulting in another revision within 5 years. However, their competing-risk estimator curves showed that even with the use of a stem diameter ≥ 15 mm in revision DFRs, the mean time to implant revision is approximately 10 years, which is still noticeably less than the mean time to implant revision for primary DFRs (18 years).…”
Section: Where Do We Need To Go?mentioning
confidence: 87%
See 2 more Smart Citations
“…Prospective single-institution, longitudinal databases are useful to expand our understanding of factors associated with successful implant outcomes, despite variability among patients treated for bone tumors who underwent reconstruction with cemented distal femoral replacement [3]. The authors of this study showed that increased stem diameter was associated with improved outcomes, and they postulated that decreasing torsional moments around the stem may further improve cemented distal femoral replacement outcomes.…”
mentioning
confidence: 99%